Overview of Post Traumatic Stress Disorder (PTSD) Symptoms of Post-Road Traffic Accident Patients - Sumitarianti Bahris; Moh Syafar Sangkala; Tuti Seniwati (Indonesian Contemporary Nursing Journal, 2020)
Introduction: Traffic accidents are one of the incidents of trauma that are at risk for PTSD. PTSD problems can occur at any age including adults. So it is necessary to screen the symptoms of Post Traumatic Stress Disorder (PTSD) post-traumatic traffic accidents, especially in adults. Method: The method of this study is Descriptive Cross Sectional used to determine the incidence of PTSD after a traffic accident. The number of samples is 30 people by taking a purposive sampling technique. The instrument used in this study es Weathers, et al.,(2013) standart instrument with a PTSD checklist for DSM-5 (PCL-5) consisting of 20 items for the disclosure of information and severity of PTSD symptoms that have been modified in Indonesian by Arnika S (2017).The technique of collecting data uses questionnaires that are given directly and filled online. Data analysis used univariate analysis. Result: The results of this study indicate that respondents who experienced PTSD after a traffic accident were 43.3% (13 people) while those who did not experience PTSD were 56.7% (17 people). As for the PTSD symptom domain, the highest number of hyperarousal symptoms is 60% (18 people) with the most types of injury being fractures and dislocations of 65% (13 people) out of 30 respondents. Conclusion: This study indicate that the symptoms of PTSD after a traffic accident. But the number of respondents who did not experience PTSD more than those who experienced PTSD. The most common symptom is hyperarousal symptoms at the onset of 11-13 weeks after a traffic accident.